Area in the West End, July 17, 1958 - York, Raymond (Tufts Archival Research Center, 2005)
Street-level view of an area in the West End. Signage adorns some of the buildings that line the street, and automobiles are parked along the curb. Pedestrians are included in the photograph. 2 5/8 x 3 15/16, 3 1/4 x 4 1/2 overall Photographs